PATH-20. ANAPLASTIC ASTROCYTOMA: WHY DOES SURVIVAL DIFFER SO MUCH FOR THE SAME HISTOLOGICAL GRADE?. (5th November 2018) - Goacher, Edward; Mathew, Ryan; Fayeye, Oluwafikayo; Chakrabarty, Aruna; Loughrey, Carmel; Feltbower, Richard; Chumas, Paul
Abstract: BACKGROUND: Increasing knowledge and understanding of the molecular genetics driving both the occurrence and transformation of gliomas has led to a more discrete and objective classification of such tumours. Both phenotypic and genotypic variations now underpin their classification, and thus help to more accurately guide their clinical management. However, WHO Grade III Anaplastic Astroyctoma (AA) remains an unpredictable, heterogeneous entity; displaying a variable prognosis, clinical course and treatment response. AIMS: To examine additional measurable tumour characteristics that may delineate overall survival (OS) more predictably in AA. METHODS: Data was collected on newly diagnosed cases of AA between 2003–2014, followed up for a minimum 3-years. Molecular information was obtained from case records and prospectively performed in cases where missing. Histological slides were manually examined for Ki67 proliferation index, cellularity and number of mitotic figures. Cox-regression and Kaplan-Meier analyses were used to assess OS. RESULTS: In total, 51 cases were included with an OS of 12months (range: 1 – 150months). Cumulative 3-year survival was 29.4%. Median age was 50years (range: 24 – 77years). Across the cohort, age, IDH1m status, oncological therapy and Ki67 were significant independent prognostic indicators on multivariate analysis (p<0.05). Median age in IDH1 wild-type (IDH1wt) tumours was significantly greater than IDH1 mutant cases (p<0.01). In cases demonstrating OS ≥3-years, Ki67 index, number of mitotic figures and percentage areas of 'high cellularity' were significantly reduced i.e. more characteristic of lower-grade/WHO Grade II glioma. Neither age nor Ki67 index had prognostic impact on IDH1wt cases. CONCLUSIONS: IDH1m status remains the most significant prognostic indicator amongst AA but Ki67 index has a significant independent prognostic value in AA. Number of mitotic figures and cellularity also offer valuable prognostic information. Further investigation utilising Ki67 quantification in standard tumour characterisation in histologically confirmed AA may aid in prognostication and inform precision medicine.